The defense of children in Andalucia: detection and intervention in Education for the protection of childhood and adolescence. Intervention from the Educational Inspection - Morales Martín, Aurora Mª Auxiliadora; Márquez Barroso, Victoriano (Avances en Supervisión Educativa, 2017)
Childhood and adolescence are shaped as fundamental pillars of our society, in them lies the future of it. Administrations, as constitutional guarantors of their proper future development, have as their unavoidable obligation their protection. The school environment is a privileged area to safeguard these fundamental rights. In the educational field, therefore, both preventive actions are necessary in the educational environment itself, as well as those of information and notification to other Specialized Services. For this purpose, educational inspection maintains as a primary duty to maintain the best interest of the child as a basis for intervention in all situations that may harm children and adolescents, from an eminently preventive approach. Prevention is one of the guiding principles of administrative action. Thus, the intervention should be carried out on progressively differentiated levels, from less to more, in primary, secondary and tertiary interventions, focusing on primary and secondary prevention in the education sector. Both the organization and the functional elements of the schools are prepared to attend to these tasks, either within the elements of the center (basic documents) or in the intervention protocols before situations of bullying, abuse or gender violence, between others. In any case, the plans of action of the Educational Inspectorate include the supervision and advisory work in these subjects as a habitual and necessary work, for which concrete measures are established within its structure and its operation.
Keywords: minor; protection; education; Andalusia; prevention; protocol; school bullying; mistreatment; gender violence; transgender